Hubungan Konsumsi Kafein dengan Kejadian Depresi - Indah Salsabila; Putu Ristyaning Ayu Sangging; Intanri Kurniati; Ratna Dewi Puspitasari (CV. Jasa Sukses Abadi, 2023)
Depression is a mood disorder. Depression is characterized by a feeling of sadness that lasts continuously and for a long time, which can interfere with a person's physical condition and social life. Around 121 million people in the world suffer from depression. It is estimated that only 30% of people with depression get proper treatment. This number does not include people who have clinical symptoms of depression but are not actually diagnosed. Some patients are also considered not to get proper treatment. The number of Indonesian populations aged more than 15 years and diagnosed with depression is 12 million sufferers. Pharmacological therapy in depressed patients is antidepressants such as serotonin and noradrenaline reuptake inhibitors (SNRIs), and selective serotonin reuptake inhibitors (SSRIs). However, there are side effects that can result from long-term use of these drugs. Therefore, other treatments such as giving herbal medicines are needed to reduce symptoms in people with depression. Giving caffeine with the right dose can reduce the risk of depression, because of its ability to block the adenosine receptor subunit. However, caffeine consumption with doses above 68mg and below 509mg per day is assessed to have the opposite effect that increases the risk of developing depression.